Comment on: "Does the Karakoram fault interrupt mid-crustal channel flow in the western Himalaya?" by Mary L. Leech, Earth and Planetary Science Letters 276 (2008) 314-322 Discussion - Searle, M; Phillips, R (2009)
Leech [Leech, M.L., 2008, Does the Karakoram fault interrupt mid-crustal channel flow in the western Himalaya? Earth Planet. Sci. Lett., 276, 314-322.] proposed that (1) Himalayan granites are significantly more abundant east of the Karakoram fault termination (around Mount Kailas, in SW Tibet) than west of it in the Zanskar-Kumaon region, that (2) the fault may have created a barrier to southward flow of mid-crustal channel flow, and that (3) the fault acted as a vertical conduit for these melts. These inferences are based upon new U-Pb SHRIMP data from the Leo Pargil dome, NW India, and the analysis of published U-Pb ages from additional Himalayan domes. Here we point out the flaws in all these hypotheses and suggest a much closer comparison of granites along the Karakoram shear zone to the widespread Miocene crustal melt granites of the Baltoro Karakoram range in North Pakistan. Field relationships combined with U-(Th)-Pb dating of granites and metamorphic rocks clearly shows that the leucogranites exhumed along the Karakoram fault are related to regional metamorphic and melting events along the Baltoro Karakoram range of the Asian plate and not to Indian plate Himalayan leucogranites at all. We discuss individually the points raised. © 2009 Elsevier B.V. All rights reserved.